UJI POTENSI ANTITUBERKULOSIS EKSTRAK n-HEKSAN DAN EKSTRAK ETANOL DAUN RIMBANG (Solanum torvum Sw.) SECARA IN VITRO - Harianti, Evi; Fatimah, Cut; Gunawan, Muhammad; Lala, Andi (Universitas Imelda Medan, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium tuberculosis which still affects many Indonesians and causes death. Currently, many people are resistant to treating tuberculosis using synthetic chemicals, so many sufferers find it difficult to recover, while the discovery of new drugs is still rare, therefore we need drugs made from natural ingredients that have been used by the community to treat coughs with phlegm and blood, which is one of the Symptoms of tuberculosis include rimbang leaves (Solanum torvum Sw.). Therefore, researchers conducted antituberculosis potential tests with rimbang leaf extract (Solanum torvum Sw.) with the aim of obtaining alternative medicines from plants that are rational, safe, cheap and easy to obtain. The extract was made by percolation using n-hexane followed by ethanol fractionation, then a phytochemical screening test was carried out on fresh leaves, simplicia, ethanol extract and n-hexane extract. The antituberculosis test of n-hexane extract and ethanol extract was carried out on Mycobacterium tuberculosis bacteria using the Lowenstein-Jensen method using patient sputum which was first identified using Ziehl Nielsen staining. The results of the phytochemical screening test showed that the chemical compound groups in fresh leaves, simplicia, ethanol extract and n-hexane extract, namely ethanol extract, were positive for alkaloids, flavonoids, glycosides, saponins, steroids/triterpenoids. and tannins while the n-hexane extract was positive for glycosides and steroids/triterpenoids. The antituberculosis effectiveness of ethanol extract is stronger than n-hexane extract, because in the 1st week and 2nd week the ethanol extract was able to inhibit the growth of Mycobacterium tuberculosis, while the n-hexane extract from the 1st to the 4th week did not inhibit the growth of Mycobacterium tuberculosis at all.